A Comparison of Computer-Based Versus Pencil-and-Paper Assessment of Drug Use. - Sarrazin, Mary S. Vaughan; Hall, James A.; Richards, Christopher (Research on Social Work Practice, 2002)
A study was conducted to investigate whether client responses to a structured interview differed when the interview was administered using a pencil and paper or a computer. Findings revealed in general clients provided the same responses in both types of interview and that there was no evidence that the use of computerized clinical assessments by social work practitioners might compromise the validity of client responses.